Mangrove Land Mapping and the Potential for Bivalve Diversity with Remote Sensing in the Pulau Dua Nature Reserve (As an Initial Study for the Development of Class X High School Ecosystem Biology Subconcept Learning Devices) - Enggar Utari; Hartanto Sanjaya; Mahrawi Mahrawi; Indria Wahyuni; Pipit Marianingsih; Ita Nurlaita (Universitas Muhammadiyah Enrekang, 2023)
Bivalvia is an invertebrate animal that has a high level of diversity and a marine biological resource that has significant economic value. This research was conducted in November 2021, aiming to determine bivalve diversity, mapping of manrove land and the potential for bivalve diversity, the relationship between the results of analysis of the presence of water on bivalves diversity in the Pulau Dua Nature Reserve and the implications of research results in the field of education. The method used is the roaming method to determine bivalves diversity and remote sensing methods to map areas of potential bivalve diversity in Pulau Dua Nature Reserve. The results of observations found that the diversity of bivalves in Pulau Dua Nature Reserve was included in the medium diversity category with a value of 1.085. The results of the relationship between bivalve diversity and MNDWI are classified as having a strong relationship, namely the correlation coefficient (r) is 0.668. In the Pulau Dua Nature Reserve, it was found that areas with a high potential for bivalve diversity were found at coordinates 106.198956 6.018374. The results of this research were then carried out to analyze the material at KD 3.10 and KD 4.10 for class X SMA at school.